ANALISIS YURIDIS ATAS TINDAK PIDANA KEKERASAN SEKSUAL TERHADAP ANAK DI KABUPATEN MAMAS: JURIDICAL ANALYSIS OF CRIME OF SEXUAL VIOLENCE ON CHILDREN IN MAMASA DISTRICT - Syam, Muh, Tomy (Faculty Of Law Bosowa University, 2022)
This study aims to (1) determine the application of criminal law against perpetrators of sexual violence, (2) to find out the judges' considerations in deciding cases of sexual violence against children, where the authors took data obtained from the results of direct interviews with the Public Prosecutor and Judges of the Polewali District Court, besides that research was also obtained through library research, namely by reviewing library materials relevant to research obtained from various literary sources, through books, print media, writings, papers and legislation. The results of the study show that (1) in the application of the law to perpetrators of criminal acts of sexual violence against children, it refers to Article 81 Paragraph (1) of Law Number 23 of 2002 concerning Child Protection as Lex Speciallis of Article 287 of the Criminal Code. (2) Judges in making decisions are based on considerations through the prosecutor's indictment letter, witness statements (both victim and defendant statements).